Optical properties of dye DN-F01 as sensitizer - Febrina Ramadhani; Agus Supriyanto; Mohd Khairul Bin Ahmad; Nadiyah El-Haq Diyanahesa; Diani Galih Saputri (Journal of Physics: Theories and Applications, 2019)
Dye-Sensitized Solar Cell (DSSC) is a solar cell made from organic material that works with an electrochemical photo system to convert solar energy into electrical energy. The components of DSSC consist of transparent conductive substrates, dyes, semiconductors, electrolytes and counter electrodes. Dye as a sensitizer is has an important role in DSSC performance improvement. This study aims to obtain optical characterization such as absorbance spectrum and transmittance from DSSC using dye DN-F01 with concentration 2x10-3 M. Optical characterization has been tested using a UV-VIS Spectrophotometer Shimadzu UV-1800. The test results show that the absorbance spectrum of the dye is at a wavelength of 400-500 nm. Band gap energy of DN-F01 has obtained  from its absorbance and transmittance value is about 2,46 eV.